2020
DOI: 10.2478/aiht-2020-71-3396
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to antimicrobial susceptibility testing of plant-derived polyphenolic compounds

Abstract: As multidrug resistance gains momentum, the last two decades have seen an ever-growing interest in the antimicrobial properties of plant extracts and plant-derived compounds. Most of the focus is on polyphenols – a large and diverse group of phytochemicals with strong antibacterial activity. Testing methods provide reliable results as long as they follow standard procedures. However, methods and procedures used in antimicrobial susceptibility testing (AST) are often too diverse to allow comparison of results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 90 publications
(105 reference statements)
4
34
0
4
Order By: Relevance
“…The antioxidant and anti-inflammatory activities of EVOO polyphenols are essentially related to their ability to attenuate reactive oxygen species (ROS), destroy carcinogenic metabolites, and act negatively on the inflammatory processes. Several studies have revealed the antioxidant and anti-inflammatory activities of EVOO polyphenols and their protective effects against several diseases [81,89,[99][100][101][102][103][104]. The antioxidant activity of EVOO is not necessarily related to its high content of total phenols.…”
Section: In Vitro Evoo Polyphenols Biological Screening: a Point Abou...mentioning
confidence: 99%
“…The antioxidant and anti-inflammatory activities of EVOO polyphenols are essentially related to their ability to attenuate reactive oxygen species (ROS), destroy carcinogenic metabolites, and act negatively on the inflammatory processes. Several studies have revealed the antioxidant and anti-inflammatory activities of EVOO polyphenols and their protective effects against several diseases [81,89,[99][100][101][102][103][104]. The antioxidant activity of EVOO is not necessarily related to its high content of total phenols.…”
Section: In Vitro Evoo Polyphenols Biological Screening: a Point Abou...mentioning
confidence: 99%
“…Still, it is crucial to standardize new techniques that can detect the effects of natural compounds against microorganisms more selectively, accurately, and more quickly. Concerning MIC, it is reported that are routinely considered antimicrobial MIC values between 100 and 1000 μg/ml, but it is not a consensus, as there are authors who believe that values below 100 μg/ml should be considered significant (Bubonja‐Šonje, Knezević, & Abram, 2020). Finally, these findings demonstrate the antibacterial potential of the Phytolaccaceae family, although more studies in vivo are mandatory.…”
Section: Resultsmentioning
confidence: 99%
“…European Committee on Antimicrobial Susceptibility Testing (EUCAST), and Clininal and Laboratory Standards Institute (CLSI) provide standard methods called antimicrobial susceptibility testing (AST) for conventional antimicrobials for rational comparison among antimicrobial assay results generated by researchers (Bubonja-Šonje et al 2020 ). Unfortunately, there are no such established methods for assessing the antimicrobial properties of plant materials due to the complexity of plant samples and this leads many researchers to adopting varied modified AST to achieve their desired goals (Bubonja-Šonje et al 2020 ). The result of these of these incoherent test methods is the generation of incomparable, difficult-to-interpret and often times misinterpreted research outcomes (Bubonja-Šonje et al 2020 ; Cos et al 2006 ; Eloff 2019 ; Gertsch 2009 ).…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Unfortunately, there are no such established methods for assessing the antimicrobial properties of plant materials due to the complexity of plant samples and this leads many researchers to adopting varied modified AST to achieve their desired goals (Bubonja-Šonje et al 2020 ). The result of these of these incoherent test methods is the generation of incomparable, difficult-to-interpret and often times misinterpreted research outcomes (Bubonja-Šonje et al 2020 ; Cos et al 2006 ; Eloff 2019 ; Gertsch 2009 ). This is what was observed in the course of this review, different researchers adopted varying test methods; different concentrations of plant samples were used; test organisms and media were not similar in many cases; and endpoint parameters (MIC, IC 50 ) assessed were dissimilar (Cos et al 2006 ).…”
Section: Pharmacological Propertiesmentioning
confidence: 99%